Effect of the Novel Coronavirus Pneumonia Pandemic on Medical Students’ Psychological Stress and Its Influencing Factors - Ye, Wan; Ye, Xinxin; Liu, Yuanyuan; Liu, Qixi; Vafaei, Somayeh; Gao, Yuzhen; Yu, Huiqin; Zhong, Yanxia; Zhan, Chenju (Frontiers in Psychology, 2020)
In December 2019, an outbreak of the novel coronavirus pneumonia infection occurred in Wuhan City, Hubei Province, China, and have received substantial attention globally. Little studies have investigated related to the psychological stress of students in Health University during the COVID-19 outbreak and almost no work has attended to its influencing factors that may cause their psychological stress risk. This cross-sectional, survey-based, region-stratified study collected demographic data and mental measurement from 2498 medical students and 1177 non-medical students in 31 provinces from March 5, 2020, to March 10, 2020, in China. The psychological stress was measured using the Chinese Perceived Stress Scales (CPSS) under a self-design questionnaire. Sociodemographic, major characteristics and knowledge of the novel coronavirus pneumonia were also identified as potential influencing factors of stress. The study revealed that medical students are suffering from more stress than non-medical students almost in all over provinces of China. Four influencing factors including, level of familiarity with the novel coronavirus, family income, major of students, and status of the intern student can be significantly related to students’ stress in the medical group by using the univariate and multivariate analysis. Further analysis showed that students with low stress had a greater number of positive psychological emotions and a lower number of negative psychological emotions than them with medical students with high stress. In, addition, high stress caused low enthusiasm for learning in these medical students and lead little/no willingness to do professional medical work in the future. In conclusion, we need to increase the level of our knowledge related to the novel coronavirus pneumonia to reduce the stress, and strongly focus on the special populations in the medical students with certain features, such as intern students, clinical nursing students, and low-income families, to improve their learning attitudes and establish positive professional mental outlooks.